2006
DOI: 10.1109/tsm.2006.883589
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Design Analysis and Yield Optimization

Abstract: Abstract-Fluctuations are inherent to any fabrication process. Integrated circuits and micro-electro-mechanical systems are particularly affected by these variations, and due to high quality requirements the effect on the devices' performance has to be understood quantitatively. In recent years it has become possible to model the performance of such complex systems on the basis of design specifications, and model-based Sensitivity Analysis has made its way into industrial engineering. We show how an efficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Rasmussen and Ghahramani [3] have shown that GP-based BMC can significantly outperform Monte Carlo importance sampling (MCIS). Several applications of the Bayes-Hermite quadrature have then been proposed in the literature and among them, the work of Pfingsten et al [4] is particularly interesting in the way they derive a closed-form solution. However, it is not suited to the particularities of spherical functions we are faced with in global illumination problems.…”
Section: Related Workmentioning
confidence: 99%
“…Rasmussen and Ghahramani [3] have shown that GP-based BMC can significantly outperform Monte Carlo importance sampling (MCIS). Several applications of the Bayes-Hermite quadrature have then been proposed in the literature and among them, the work of Pfingsten et al [4] is particularly interesting in the way they derive a closed-form solution. However, it is not suited to the particularities of spherical functions we are faced with in global illumination problems.…”
Section: Related Workmentioning
confidence: 99%
“…Although the theory of Bayesian Quadrature has been known since 1991 [O'H91], it is only recently that it has been put into practice (e.g. [PHR06, KNKS08]) and to the authors' knowledge, no research in this direction has yet been reported in the computer graphics literature. In the field of global illumination, most research works are based on importance sampling and although this variance reduction technique can be applied to many cases (e.g.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, magnetometers adopted multiphysics-based optimization and nonlinear situations [ 14 ], and gyroscopes focused on the packaging with double yield [ 15 ]. Except for unique device analysis, methods that are generally applicable have advanced the processing improvement further [ 3 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Mirzazaden et al [ 16 , 17 , 18 ] investigated morphology uncertainties with reduced-order models through on-chip tests.…”
Section: Introductionmentioning
confidence: 99%
“…For those non-linear actuated MEMS devices, high fidelity optimization schemes have also been realized. To avoid the brute-force Monte Carlo (MC) scheme, Pfingsten et al [ 21 ] considered a Bayesian Monte Carlo approach for yield estimation, with 90.0% computational savings but the same accuracy, compared with MC schemes. Vudathu et al [ 22 , 26 ] applied a sensitivity analyzer for MEMS (SAM) by worst-case analysis, revealing the effects of parametric variations on performance and yield.…”
Section: Introductionmentioning
confidence: 99%